The someday suitcase - Haydu, Corey Ann (Katherine Tegen Books, 2018)
Ten-year-old best friends Clover and Danny share a connection that goes beyond friendship--Clover is certain its symbiotic. When Danny starts getting sick and has to undergo trips to the hospital to see specialist who search for a diagnosis, Clover becomes increasingly convince they cannot survive without one another. And as Danny grows sicker, Clover worries time is running out for them to pack the purple suitcase they got for their future trips together.